PENGARUH PEMBERIAN PUPUK KANDANG DAN PUPUK HAYATI TERHADAP HASIL DAN KUALITAS TANAMAN KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA - Karya; Endang Kantikowati (Program Studi Agroteknologi Faperta UNIBBA, 2026)
This study aimed to determine the effect of chicken manure and biofertilizer on the growth and yield of Granola variety potatoes (Solanum tuberosum L.). The study was conducted in Lebak Saat Hamlet, Tribaktimulya Village, Pangalengan District, Bandung Regency, West Java Province, at an altitude of 1,200 m above sea level. This study used a factorial randomized block design (RBD) with three replications. Factor I: Chicken manure dose (k1 = 5 tons/ha, k2 = 10 tons/ha, k3 = 15 tons/ha). Factor II: Biofertilizer concentration (h1 = 2.5 ml/l, h2 = 5.0 ml/l, h3 = 7.5 ml/l). The parameters observed were the number and weight of tubers per plant. The results showed that the chicken manure dose and biofertilizer concentration treatments significantly affected the number and weight of tubers per plant, as well as the weight of tubers per plot. There was an interaction between the dose of chicken manure and the concentration of biofertilizer on the number of tubers per plant, tuber weight per plant, and tuber weight per plot. The highest yield was shown by the k2h3 treatment combination (a dose of chicken manure of 10 tons/ha and a concentration of biofertilizer of 7.5 ml/l). Yielded 55.30 kg per plot (1.26 kg per plant).